Studying Tourism Impacts by Q Methodology Approach - HAVLIKOVA, Michaela (Journal of Environmental Management and Tourism, 2016)
This paper presents the results of a Q-methodology survey conducted at the Karlovy Vary film festival. The festival, held annually in July, has been going for almost fifty years, in Karlovy Vary, Czech Republic. The purpose of this research is to enhance the current literature on evaluating tourism and event impacts, specifically relating to the relationship between the guest and the host. The paper compares the results of a 5-pile Q-set survey and a 7-pile Q-set survey. Cluster analysis and an ANOVA test were applied to compare the results. The results show significant differences between both types of survey, although some commonalities were observed.
Keywords: tourism; event; Q-methodology; cluster analysis